DEFLECTIONS OF REINFORCED AND NON-REINFORCED BEAMS OF RECTANGULAR SECTION OF GLUED WOOD (Collection of scientific works «Modern structures of metal and wood», 2022)
The  dynamic  development  and  distribution  of  glued  timber  structures  in construction predetermine their comprehensive study. The issue of increasing the load capacity of such structures using reinforcement is also relevant. The reinforcing of timber elements using steel reinforcement is more researched, but recent studies have shown good use of synthetic fiber-based composites as reinforcement for timber structures.  Our purpose was to combine these two types of reinforcement and to investigate the stiffness change of the specimens in the form of glued timber beams.  Several series of beams with cross-sectional dimensions of 100x150 mm and 3000 mm length were prepared for the research. The first series consisted of two glued unreinforced beams. They were tested to determine the fracture load, to establish control deflections and to compare them with the corresponding  deflections  of  reinforced  beams.  The  second  series  consisted  of  two  glued  timber beams, which were reinforced with two 12 mm diameter steel rods in the compressed zone and with Sika Carbo Dur S-512 carbon fiber tape reinforcement in the stretched zone. The third series included two beams, which were reinforced with 16 mm diameter steel reinforcement in the compressed zone and the Sika Carbo Dur S-512 carbon fiber tape reinforcement in the stretched zone. The fourth series included one beam, which was reinforced with only steel reinforcement in the shape of two 12 mm diameter  rods  in  the  compressed  zone.  The  test  specimens  were  loaded  using  a  jack  by  two concentrated loads. The deflections of all beams were measured using the deflection indicators. As a result  of  experimental  studies,  comparative  graphs  of  the  variation  of  deflections  versus bending moment were constructed. The specimens of the second series with reinforcement of 12 mm diameter in the compressed zone were the most rigid. The ultimate deflection for them was achieved at load, which is 61% more than the average value for unreinforced samples. The ultimate deflection value for the third series of beams was achieved at loading, on average, 39% higher than for unreinforced beams. However, it should be noted that the carrying capacity of these samples was the highest. The reinforcing of the beam of the fourth series did not increase the rigidity, since the ultimate deflection was achieved at the same load values, as for the unreinforced glued timber samples.